Analisis Pengaruh Ukuran Perusahaan, Current Asset dan Leverage terhadap Pemilihan Metode Akuntansi Persediaan - Ulfa Narulita; Eko Hadi Siswanto (Indonesian Journal of Economics Application (IJEA), 2020)
Analysis of the Effect of Company Size, Current Assets, and Leverage on the Selection of Inventory Accounting Methods (Case Study of Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2012-2018 Period). The purpose of this study is to test and empirically prove the influence of company size, current assets, and leverage on the selection of inventory accounting methods. The sample in this study were food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2012 to 2018, which were selected using the purposive sampling method. Twelve companies meet the criteria. Eleven companies use FIFO, and one company uses the standard method. Tests conducted in this study include hypothesis testing. Hypothesis testing is done using logistic regression with the enter method and a significance level of 5%. The testing of this study was carried out with the help of the IBM SPSS Statistics version 23 computer program. The results of the hypothesis test showed that only firm size affected the inventory accounting method. Whereas company size and current assets and leverage do not affect company accounting methods.